PREVALENCE OF CONGENITAL SYPHILIS IN SANTA CASA DE MISERICÓRDIA OF ANÁPOLIS (CIPEEX, 2022)
SYPHILIS IS AN INFECTIOUS, SYSTEMIC, PREVENTABLE DISEASE THAT, WHEN NOT TREATED EARLY, MAY PROGRESS TO A CHRONIC CONDITION WITH IRREVERSIBLE SEQUELAE. IT IS TRANSMITTED SEXUALLY AND VERTICALLY, RARELY VIA BLOOD TRANSFUSION. CONGENITAL SYPHILIS CORRESPONDS TO INFECTION OF THE FETUS BY TREPONEMA PALLIDUM, BEING TRANSPLACENTALLY TRANSMITTED AT ANY MOMENT OF GESTATION, REGARDLESS OF THE CLINICAL STAGE OF THE DISEASE IN THE PREGNANT WOMAN. THE INFECTION CAN HAVE SERIOUS CONSEQUENCES FOR THE CONCEPT: ABORTION, FETAL DEATH AND MOTOR, COGNITIVE, NEUROLOGICAL, VISUAL AND AUDITORY SEQUELAE. VERTICAL TRANSMISSION IS KNOWN TO BE AVOIDABLE, PROVIDED THAT THE PREGNANT WOMAN IS DIAGNOSED EARLY AND ADEQUATELY TREATED. IN ANNAPOLIS, THERE IS A HIGH PREVALENCE OF SYPHILIS, SO IT IS TO BE EXPECTED THAT, BECAUSE OF THIS, THERE IS A HIGH NUMBER OF CASES OF CONGENITAL SYPHILIS IN THE CITY. THEREFORE, THIS STUDY AIMS TO CORRELATE THE HIGH PREVALENCE OF SYPHILIS IN ANNAPOLIS WITH THE POSSIBLE INCREASE IN THE NUMBER OF CASES OF CONGENITAL SYPHILIS IN SANTA CASA DE MISERICÓRDIA DE ANÁPOLIS. IN ORDER TO DO SO, THE PROFILE OF THE PREGNANT WOMAN, IN RELATION TO THE AGE GROUP, LEVEL OF EDUCATION, WHETHER OR NOT PRENATAL CARE AND DIAGNOSIS DURING PREGNANCY OR POSTPARTUM AND ADHERENCE TO THE TREATMENT WILL BE OBSERVED. THIS WILL BE A LONGITUDINAL, DESCRIPTIVE AND QUALITAIQUANTITATIVE STUDY. THUS, IT IS EXPECTED TO FIND A SIGNIFICANT INCREASE IN CASES OF CONGENITAL SYPHILIS, RELATED TO THE HIGH PREVALENCE OF SYPHILIS IN THE CITY OF ANÁPOLIS. ALSO, IT IS INTENDED TO ASSOCIATE INEFFECTIVE PRENATAL PRACTICE AND / OR LATE DIAGNOSIS OF SYPHILIS IN THE PREGNANT WOMAN WITH AN INCREASE IN THE PREVALENCE OF CONGENITAL SYPHILIS. FINALLY, IT IS EXPECTED TO BE ABLE TO EVALUATE THE EFFICACY OF THE TREATMENT AND ITS RELATION WITH THE DECREASE OF THE CASES OF CONGENITAL SYPHILIS.
Keywords: Syphilis. Congenital syphilis. Santa Casa de Misericórdia de Anápolis.